1996
DOI: 10.1159/000097237
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Interleukins, ACTH, Cortisol and Prolactin Concentrations in the Blood of Patients with Parkinson's Disease

Abstract: Parkinson''s disease (PD) is characterized by a markedly decreased number of nigrostriatal dopaminergic neurons. The pathogenesis of PD is still unknown; among other etiological factors, immunological abnormalities have been suggested. Recently, interleukin-2 (IL-2) has been hypothesized to be an endogenous cytokine that regulates striatal dopaminergic function. We examined the plasma concentrations of IL-1, IL-2, IL-6 and blood levels of ACTH, Cortisol and prolactin of 21 patients with PD without any previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
0
4

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(61 citation statements)
references
References 0 publications
2
55
0
4
Order By: Relevance
“…Amplified levels of the cytokines TNF-α, IL-2, IL-6 and RANTES (Brodacki et al, 2008;Dobbs et al, 1999;Rentzos et al, 2007;Stypula et al, 1996) have also been detected in serum obtained from PD patients. It has been proposed that increases in these serum cytokine levels may serve as a therapeutic marker for PD, based on a blood sample study of men with high plasma concentrations of IL-6 correlating with an increased risk of developing PD (Chen et al, 2008b).…”
Section: Systemic Cytokinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Amplified levels of the cytokines TNF-α, IL-2, IL-6 and RANTES (Brodacki et al, 2008;Dobbs et al, 1999;Rentzos et al, 2007;Stypula et al, 1996) have also been detected in serum obtained from PD patients. It has been proposed that increases in these serum cytokine levels may serve as a therapeutic marker for PD, based on a blood sample study of men with high plasma concentrations of IL-6 correlating with an increased risk of developing PD (Chen et al, 2008b).…”
Section: Systemic Cytokinesmentioning
confidence: 99%
“…Proinflammatory cytokines IL-1β, TNF-α, IL-2, IL-6 and IFN are constitutively expressed at basal levels in PD patients as demonstrated in post-mortem brains, serum and cerebrospinal fluid in vivo (Boka et al, 1994;Dobbs et al, 1999;Mogi et al, 1994a, b;Mount et al, 2007;Stypula et al, 1996). Moreover, the death signalling receptor TNF receptor type-1 (TNFR-1) 9 is expressed on dopaminergic neurons in human SNpc (Boka et al, 1994;Mogi et al, 2000).…”
Section: Neuroinflammation In Parkinson's Diseasementioning
confidence: 99%
“…A few studies also reported altered levels of serum inflammatory markers in PD patients [552][553][554]. In rats, chronic infusion of bacterial endotoxin lipopolysacharide (LPS) into substantia nigra resulted in activation of microglia followed by degeneration of dopaminergic neurons [555], suggesting that inflammation may precede neurodegeneration.…”
Section: Inflammationmentioning
confidence: 99%
“…In support of a role for systemic immune cells in the degeneration of nigral DA neurons, CD4 -/-mice have been shown to be resistant to MPTP-induced neurotoxicity in the SN (Brochard et al, 2009). Amplified TNF , IL-2, IL-6 and RANTES (Brodacki et al, 2008;Dobbs et al, 1999;Rentzos et al, 2007;Stypula et al, 1996) levels have also been detected in serum obtained from PD patients. Increases in serum cytokines may serve as a therapeutic marker for PD as a blood sample study of men with high plasma concentrations of IL-6 revealed an increased risk of developing PD (H. .…”
Section: Systemic Inflammation and Parkinson's Diseasementioning
confidence: 96%
“…Cytokines produced by LPS-stimulated microglia can potentiate microglial activation through autocrine signalling to create a self-propagating cycle of expression. Pro-inflammatory cytokines IL-1 , TNF , IL-2 and IL-6 are constitutively expressed at basal levels in PD patients as evidenced in post-mortem, serum and cerebrospinal fluid in vivo (Boka et al, 1994;Dobbs et al, 1999;Mogi et al, 1994a;Mogi et al, 1994b;Stypula et al, 1996). Moreover, the death signalling receptor TNF receptor type-1 (TNFR-1) is expressed on DA neurons in human SNpc (Boka et al, 1994;Mogi et al, 2000).…”
Section: Activated Microglia In Parkinson's Diseasementioning
confidence: 99%